Phytoextract-assisted synthesis of Fe2O3/MgO nanocomposites for efficient photocatalytic degradation of gentian violet - Tedla, Haileyesus; Goddati, Mahendra; Wondemagegnehu, Eshetu Bekele; Tufa, Lemma Teshome; Mekonnen, Andualem; Lee, Jaebeom (Frontiers in Environmental Chemistry, 2024)
Organic-based pollutants are extensively released from various industries, and they are potentially harming the environment and human health. Photocatalysis is regarded as one of the most promising techniques for degrading organic contaminants from wastewater. Therefore, in this study iron oxide-based nanocomposite was synthesized by an emerging green and sustainable method using Ethiopian endemic plant extract, Echinops kebericho M. as a capping and stabilizing agent. The phytoextract-assisted synthesized nanoparticles (NPs) α-Fe2O3 and nanocomposites (NCs) α-Fe2O3/MgO calcinated at a temperature of 400 °C were characterized and taken for their photocatalytic activities towards gentian violate dye (GV) degradation using Ultraviolet-Visible Spectroscopy (UV-Vis) at optimized catalyst dose, initial GV concentration, pH and time conditions. The X-ray diffraction (XRD) analysis result revealed that the mean crystal size of α-Fe2O3 and α-Fe2O3/MgO is 11.2 nm and 15.4 nm, respectively. Characterization results of scanning electron microscope coupled with energy-dispersive X-ray spectroscopy (SEM-EDS), transmission electron microscope (TEM), high-resolution transmission electron microscope (HRTEM), and X-ray photoelectron spectroscopy (XPS) clearly showed the successful deposition of MgO on α-Fe2O3. The maximum degradation of GV, 96.2% was observed by using α-Fe2O3/MgO after 60 min under visible light irradiation. Thus, synthesized NCs were shown better GV degradation efficiency in a shorter time as compared to the previously reported nanomaterials.The results revealed photocatalytic degradation using endemic plant extract-assisted synthesized NCs, α-Fe2O3/MgO is considered as a greener, simple and more efficient method for the removal of organic dyes.